2021
DOI: 10.1186/s13690-021-00638-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors contributing to occupational health inequality in Korea: a cross-sectional study using nationally representative survey data

Abstract: Background Despite the consensus that higher occupational classes tend to have better health and lower mortality rates, one study has reported reversed occupational gradients in mortality rates among Korean men after the economic crisis in the late 2000s. To examine these patterns of health inequality in more detail, we investigated the tendency of occupational gradients in socioeconomic position and multiple pathway indicators known to affect mortality in Korea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…The mortality estimates of the “others” group were exceptionally higher than those of non-manual workers, and this discrepancy was statistically significant. Moreover, our recent study using data from the late 2000s showed that psychosocial factors (e.g., depression, stress, suicidal ideation), work environment, and health behaviors related to cancer (e.g., smoking, high-risk alcohol consumption) were more favorable in non-manual workers than in manual workers [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mortality estimates of the “others” group were exceptionally higher than those of non-manual workers, and this discrepancy was statistically significant. Moreover, our recent study using data from the late 2000s showed that psychosocial factors (e.g., depression, stress, suicidal ideation), work environment, and health behaviors related to cancer (e.g., smoking, high-risk alcohol consumption) were more favorable in non-manual workers than in manual workers [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result contradicts the prior claim of reversed mortality inequality by occupational class in Korea, which might be attributed to the denominator-numerator bias that has been commonly raised as a concern in health inequality research using unlinked data. If the census and death data by occupational class are not individually linked, as was the case in the study that proposed the inequality reversal, it is highly likely that the mortality estimates of non-manual workers will be overestimated and those of manual workers underestimated [ 9 - 12 ]. Analyzing the linked data provided via the nationally representative KNHANES (2007-2015) and individual mortality data (2007-2018), this study confirmed that even after the economic crisis of the 2000s, patterns of mortality inequality in Korea remain disadvantageous for those in lower occupational classes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations